Determination of Rice Husk Silica Effect on SOFC SDC’S Electrolyte Through Material Properties Characterization - Azam, Haziq Irham; Azmi, Mohd Azham (Research Progress in Mechanical and Manufacturing Engineering, 2024)
This thesis delves into the comprehensive characterization of Solid Oxide Fuel Cell (SOFC) electrolytes, incorporating Rice Husk Silica (RHS SiO2) and Samarium Doped Ceria (SDC). SOFCs present an enticing prospect for electricity generation with exceptional efficiency and minimal environmental impact. However, the high operational and fabrication costs, notably during the sintering process for SOFC components, pose substantial economic challenges for large-scale industries. The primary objectives are to produce SOFC electrolytes with RHS SiO2 as an additive and to determine the properties of the resulting SDC/RHS composite. The experimental methodology involves meticulous combinations of rice husk silica with SDC, utilizing predetermined parameters. This encompasses the calcination of rice husk, sintering of RHS-filled SDC, and conducting chemical and physical tests for electrolyte characterization. Results from elemental phase analysis reveal dominant cerium (Ce) composition, with oxygen (O), samarium (Sm), and silica (Si) following. Fourier Transform Infrared (FTIR) analysis, despite noise interference, indicates the incorporation of new bonding elements with silica addition and varying sintering temperatures. In conclusion, the correlation between sintering temperature, phase, and elemental composition showcases a significant influence on silica purity and porosity. Higher silica purity at increased sintering temperatures reduces porosity, providing crucial insights for optimizing SOFC performance.